Correctional method on hard core drug addicted: A study on AADK, AADK-I and INABAH - Maamor, Selamah; Abd. Wahab, Norazlina; Abdul Ghani, Abdullah; Aziz, Ahmad Bashir; Ahmad Razimi, Mohd Shahril; Elias, Nor Hanim; Nik Abdullah, Nik Safiah (Akademia Baru, 2017)
This article is part of a larger study on the role of spirituality in correcting the hard core drug addict.The study seeks to reveal the experience of former hard core drug addicted through different correctional method. This is to better understand the deep meanings from their experiences with spirituality and transformation as they cope with the challenges of drug addict. Data were gathered using in depth interview with the former drug addicted who have experience through AADK, AADK-i and Pondok Inabah.Qualitative methods were used in identifying several themes which 1) Basic method of treatment used; 2) Special treatment used; 3) Feeling during treatment; 4) Preparation to face community; 5) Successful rate.The study suggests that former drug addict experiences with drug addict and their learning processes must be understood within the appropriate cultural context.The common emphasis of spirituality on relationship with God, self and others, may significantly influence how people learn to live without drug.